Co‐Motif Discovery Identifies an Esrrb‐Sox2‐DNA Ternary Complex as a Mediator of Transcriptional Differences Between Mouse Embryonic and Epiblast Stem Cells23. (12th February 2013) - Hutchins, Andrew Paul; Choo, Siew Hua; Mistri, Tapan Kumar; Rahmani, Mehran; Woon, Chow Thai; Keow Leng Ng, Calista; Jauch, Ralf; Robson, Paul
Abstract: Transcription factors (TF) often bind in heterodimeric complexes with each TF recognizing a specific neighboring cis element in the regulatory region of the genome. Comprehension of this DNA motif grammar is opaque, yet recent developments have allowed the interrogation of genome‐wide TF binding sites. We reasoned that within this data novel motif grammars could be identified that controlled distinct biological programs. For this purpose, we developed a novel motif‐discovery tool termed fexcom that systematically interrogates ChIP‐seq data to discover spatially constrained TF–TF composite motifs occurring over short DNA distances. We applied this to the extensive ChIP‐seq data available from mouse embryonic stem cells (ESCs). In addition to the well‐known and most prevalent sox‐oct motif, we also discovered a novel constrained spacer motif for Esrrb and Sox2 with a gap of between 2 and 8 bps that Essrb and Sox2 cobind in a selective fashion. Through the use of knockdown experiments, we argue that the Esrrb‐Sox2 complex is an arbiter of gene expression differences between ESCs and epiblast stem cells (EpiSC). A number of genes downregulated upon dual Esrrb/Sox2 knockdown (e.g., Klf4, Klf5, Jam2, Pecam1 ) are similarly downregulated in the ESC to EpiSC transition and contain the esrrb‐sox motif. The prototypical Esrrb‐Sox2 target gene, containing an esrrb‐sox element conserved throughout eutherian and metatherian mammals, is Nr0b1. Through positive regulation of this transcriptional repressor, we argue the Esrrb‐Sox2 complex promotes the ESC state through inhibition of the EpiSC transcriptional program and the same trio may also function to maintain trophoblast stem cells. STEM CELLS 2013;31:269–281